Μελέτη ιδιοτήτων υπέρ-καθαρού νερού μετά από κυκλοφορία σε σωλήνες NAFION - Ζαφείρης, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανικών Μεταλλείων Μεταλλουργών. Τομέας Μεταλλουργίας και Τεχνολογίας Υλικών. Εργαστήριο Επιστήμης & Τεχνολογίας Προστασίας Περιβάλλοντος στη Μεταλλουργία & Τεχνολογία Υλικών, 2017)
This study focuses on ascertaining the existence of, and offering an explanation on, a thus far incomprehensible phenomenon which might be described as an unexpected rise of conductivity that a body of water consistently exhibits after traveling through a short, small diameter, NAFION™ tube. In conducting this study the most fundamental properties of NAFION™ were studied, mostly by examining published literature relevant to Proton Exchanging Membranes. Furthermore, some basic properties of water were reviewed, with the purpose of discovering hints as to the explanation of the incomprehensible phenomenon described earlier. Firstly, this study analyses the most fundamental properties of NAFION™ with emphasis on understanding the morphology and microstructure that it exhibits when it interacts with water, most commonly in a Fuel Cell set-up, as well us a short review of the basic properties of water itself. Secondly, the experiments conducted to ascertain and study the phenomenon are described and new results are presented. Finally, several possible explanations of the phenomenon are considered, with emphasis on, a thorough examination of, and some additional literature review on the one considered the prevailing mechanism in the explanation so far.